The Effect Of Mudharabah Financing, Musyarakah Financing and Profit Sharing Ratio On Profitability (ROA) With Non Performing Financing As Moderating Variable - Rekno Sawiji Lestari; Saiful Anwar (UIN Salatiga, 2021)
The purpose of this study was to determine the effect of Mudharabah Financing, Musyarakah Financing and Profit Sharing Ratio on Profitability with Non Performing Financing as Moderating Variable in Islamic Commercial Bank. The sample used in this study was 9 banks with the sampling technique using purposive sampling. The analytical method used is multiple linear regression. The result show that the variable Mudharabah Financing has a positive and significant effect on Profitability. While Musyarakah Financing and Profit Sharing Ratio has no effect on Profitability. And Non Performing Financing can moderate the offect of Mudharabah Financing and Profit Sharing Ratio on Profitability. But cannot moderate the effect of Musyarakah Financing on Profitability.